Along‐axis hydrothermal flow at the axis of slow spreading Mid‐Ocean Ridges: Insights from numerical models of the Lucky Strike vent field (MAR). (22nd July 2014) - Fontaine, Fabrice J.; Cannat, Mathilde; Escartin, Javier; Crawford, Wayne C.
Abstract The processes and efficiency of hydrothermal heat extraction along the axis of mid‐ocean ridges are controlled by lithospheric thermal and permeability structures. Hydrothermal circulation models based on the structure of fast and intermediate spreading ridges predict that hydrothermal cell organization and vent site distribution are primarily controlled by the thermodynamics of high‐temperature mid‐ocean ridge hydrothermal fluids. Using recent constraints on shallow structure at the slow spreading Lucky Strike segment along the Mid‐Atlantic Ridge, we present a physical model of hydrothermal cooling that incorporates the specificities of a magma‐rich slow spreading environment. Using three‐dimensional numerical models, we show that, in contrast to the aforementioned models, the subsurface flow at Lucky Strike is primarily controlled by across‐axis permeability variations. Models with across‐axis permeability gradients produce along‐axis oriented hydrothermal cells and an alternating pattern of heat extraction highs and lows that match the distribution of microseismic clusters recorded at the Lucky Strike axial volcano. The flow is also influenced by temperature gradients at the base of the permeable hydrothermal domain. Although our models are based on the structure and seismicity of the Lucky Strike segment, across‐axis permeability gradients are also likely to occur at faster spreading ridges and these results may also have important implications for the cooling of young crust at fast and intermediate spreading centers.